2022
DOI: 10.1109/jphot.2022.3195935
|View full text |Cite
|
Sign up to set email alerts
|

An All-Optical Ka-Band Microwave Long-Distance Dissemination System Based on an Optoelectronic Oscillator

Abstract: We proposed an all-optical Ka-band microwave long-distance dissemination system based on an optoelectronic oscillator (OEO). In this system, a single tone with high spectrum purity and low phase noise is excited by an injection-locked OEO, and distributed to the remote site through the fiber loop of the OEO at the same time. The second harmonic of the reference signal modulates the round-tripping optical signal at the local site, which achieves the phase conjugator at the optical domain. At the remote end, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For simplicity, we will analyze the case of only one remote antenna unit, however, the corresponding principles apply to any remote base station with the same configuration. In our previous studies, it has been shown that a similar structure can suppress phase fluctuation caused by fiber temperature drift and achieve stable transmission of a single frequency [19], [20]. In this paper, we derive in detail the process of automatic elimination of dispersion and explain the structural principles of vector signal generation without precoding modulation verification.…”
Section: System Architecture and Operation Principlementioning
confidence: 98%
“…For simplicity, we will analyze the case of only one remote antenna unit, however, the corresponding principles apply to any remote base station with the same configuration. In our previous studies, it has been shown that a similar structure can suppress phase fluctuation caused by fiber temperature drift and achieve stable transmission of a single frequency [19], [20]. In this paper, we derive in detail the process of automatic elimination of dispersion and explain the structural principles of vector signal generation without precoding modulation verification.…”
Section: System Architecture and Operation Principlementioning
confidence: 98%